Meta-Analysis the Effect of Obesity and Stress on Menstrual Cycle Disorder - Annarahayu, Lutfi; Dewi, Yulia Lanti Retno; Adriyani, Rita Benya (Journal of Maternal and Child Health, 2021)
Background: There are many factors that influence menstrual patterns to become irregular, including stress and obesity. Menstrual cycle irregularities can have a serious impact on women's health, which will affect the metabolic, fertility, sexual and reproductive systems. This study aims to analyze the influence of obesity and stress on menstrual cycle disorders with a meta-analysis study. Subjects and Method: This study is a systematic study and meta-analysis, with the following PICO, Population= women of childbearing age. Intervention= obesity and stress. Comparison = not obese and not stressed. Outcome = disruption of the menstrual cycle. The articles used in this study were obtained from several databases, including PubMed, ScienceDirect and Google Scholar. The keywords used are "menstrual disorder and obesity and stress", "obesity and menstrual irregularity", "obesity OR stress AND menstrual irregularity OR cross sectional study". The articles included in this study are full text articles with a cross sectional study design. Articles were collected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application. Results: Meta-analysis of 8 observational studies showed that obese women were 4 times more likely to have menstrual cycle disorders than normal weight (aOR= 4.19; 95% CI= 1.99 to 8.84; p= 0.002). Meta-analysis of 6 observational studies showed that women with stress had a risk of experiencing menstrual cycle disorders 1.28 times compared to women who did not experience stress (aOR= 1.28; 95% CI= 1.13 to 1.45; p = 0.001). Conclusion: Obesity and stress affect menstrual cycle disorders.